LITERARY NORMS AND SPEECH CULTURE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with the analysis of literary norms and speech culture  in the culture of speech.